SISTEM MANAJEMEN PENGOLAHAN LIMBAH CAIR DI RUMAH SAKIT UMUM DAERAH KOTA PRABUMULIH - Sri Suparni (Repository STMIK Prabumulih, 2021)
Framework of the research is to describe that hospitals in conducting its activities generate wastewater that are physical, chemical and biological. Implementation of wastewater treatment include catcher tub fat, waste water tank, tub filter, floatasi tub, sedimentation basin, tub equalization, biodetok tub FBK10, biodetok tub FBK20, tub disinfection (chlorine), disinfection contact basin, tub bioassay, sludge dryer tub. The purpose of this study was to determine the wastewater treatment process at the WWTP (Waste Water Treatment Plant) in the city General Hospital Prabumulih. In line with the problem and research objectives, this study carried out by the method of describing is descriptive about the Wastewater Treatment at City General Hospital Prabumulih by way of observation, interviews, and find sources of library. Existing research results can be concluded that the Process of Waswater Treatment in the General Hospital Prabumulih City has implemented quite well, but need to be considered again for installation of water flow gauges and how maintance WWTP (Weste Water Treatment Plant) to comply with applicable regulations and avoid occupational diseases.